Corruption risk and education at regional level - István János Tóth; Miklós Hajdu (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
In this study, we investigate the correlation between corruption risk and the level of education in European sub-national regions (NUTS2 level) between 2006 and 2020 in 16 member countries. We use the data of Tenders Electronic Daily (TED) covering the parameters of 6,766,274 public procurement contracts in total and NUTS2 level Eurostat data. We found that higher educational attainment is associated with lower corruption risk and a higher level of control of corruption, indicating that better-educated locals may force authorities to limit corruption risk as they have less tolerance for corrupt behavior. In addition, the results point out that the increasing level of education is associated with a decreasing level of corruption risk. Our study contributes to corruption research by using objective indicators characterizing the NUTS2 regions of some European countries.
Keywords: D73; H57; H75; I25; R11; 330; regions in Europe; education; corruption risk